Recurrent relations for the solutions of an infinite system of linear algebraic equations - Gomilko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain recurrent relations for bounded solutions of the system of equations $$X_k - \sum\limits_{n = 0}^∞ {\frac{{(k + n)!}}{{k!n!}}} α ^{k + n + 1} x_n = f_{k,} k = 0,1,..., α \in (0,1/2),$$ with right-hand sides {f k } k=0 ∞ ={δ kj } k=0 ∞ ,j=0,1,..., where δ kj is the Kronecker symbol.